FINANCIAL PERFORMANCE ANALYSIS AT PT. MANDIRI SYARIAH BANK - Akhmadi Akhmadi; Sumantri Sumantri; Albetris Albetris (Dinasti Publisher, 2020)
Analysis of the Growth of the Liquidity Ratio, Solvency, and Profitability, the objectives are, namely, the first is to determine the condition of the Growth of the Liquidity Ratio of PT. Bank Syariah Mandiri Indonesia for the period 2014-2018. The second is to determine the condition of the Growth of the Solvency Ratio of PT. Bank Syariah Mandiri Indonesia for the period 2014-2018. The third is to determine the Growth of the profitability ratio at PT. Bank Syariah Mandiri Indonesia for the period 2014-2018. And lastly, to determine the condition of the Growth of the Liquidity Ratio, Solvency, and Profitability with a financial performance at PT. Bank Syariah Mandiri Indonesia for the period 2014-2018. Based on the results of research conducted at PT. Bank Syariah Mandiri Indonesia it can be concluded that the average growth Liquidity Ratio 2014-2018 period be seen from the Current Ratio approach amounted to 1, 32 %. seen from the average Growth of the Solvency Ratio for the 2014-2018 period of (1) %. And the Growth of the Profitability Ratio for the 2014-2018 period is seen from the average Growth of Net Profit Margin of 140, 04 %. Return On Investment. For an average Growth of 208, 02 %. Return On Equity has an average Growth value of 192, 48 %.